EFEKTIVITAS PENATALAKSANAAN HEMOROID DENGAN PARAN INJECTION LIGATION FOR AMBEIEN (PILA) DAN HEMOROIDEKTOMI - Primitha Indriatni Serdi; Jacky Tuamelly; Nathalie Elischeva Kailola; Is Ikhsan Hataul; Presli Glovrig Siahaya; Achmad Tuahuns (PAMERI, 2023)
Hemorrhoids are a disease that arises due to the dilation of blood vessels in the hemorrhoidal plexus so it becomes a dangerous disease and can interfere with daily activities. Hemorrhoidectomy is a procedure for treating hemorrhoids by excising as little as possible only the tissue that is dilated so that it does not interfere with the work function of the anal sphincter. Paran Injection Ligation for Hemorrhoids (PILA) is another procedure to treat hemorrhoidal patients using a combination method of sclerotherapy and rubber band ligation. This study aims to compare the effectiveness of the management of hemorrhoids with PILA and hemorrhoidectomy in Tk. II. Prof. Dr. J. A. Latumeten Ambon hospital for the period October 2021- October 2022. This study was an observational analytic study using a total sampling technique with a total sample of 67 subjects, including 32 hemorrhoidal patients who received PILA treatment and 35 hemorrhoidal patients who received hemorrhoidectomy. The data used in this study were medical records of hemorrhoids at the Tk. II Prof. Dr. J. A. Latumeten Ambon hospital for the period October 2021 – October 2022. This study used bivariate analysis using the Chi-Square test to assess the effectiveness of treatment by comparing several components of management effectiveness, namely pain, bleeding, mobilization, length of stay, and postoperative visits with complications to hemorrhoidectomy and PILA. Analysis with the Fisher Exact test is used if the data does not meet the requirements for the Chi-Square Test. The results of the study showed that there were significant differences between the management of hemorrhoids and hemorrhoidectomy and PILA which were obtained from the comparison of the effectiveness components, namely; pain (p = 0.000), bleeding (p = 0.000), mobilization (p = 0.000), length of stay (p = 0.000), and postoperative visits with complications (p = 0.002) with hemoroid management (PILA and hemorrhoidectomy).